Compare nasal endoscopy with Computed Tomography scans for chronic rhinosinusitis detection in adult Iraqi patients - lafta Salman , Ali (Diyala Journal of Medicine, 2024)
Background: Chronic rhinosinusitis (CRS) is often diagnosed based on clinical features. Assurance in this context is based on the finding of inflammatory features during nasal endoscopy and computed tomography (CT) scans of the paranasal sinuses. While a CT scan is considered the most reliable method, research has shown that nasal endoscopy is also valuable and can sometimes provide additional information to supplement the CT scan in diagnosing CRS. Objective: The study goal was to demonstrate the comparative reliability of nasal endoscopy and computed tomography scans in diagnosing chronic rhinosinusitis in adult patients treated at Baqubah Teaching Hospital. Patients and Methods: The study sample consisted of consecutive adult participants clinically diagnosed with chronic rhinosinusitis. Patients who had a computed tomography scan of the paranasal sinuses and a nasal endoscopy during three months were the subjects of this investigation; the outcomes were linked. Results: Study results exhibit that the most prevalent symptoms seen in the study participants were nasal discharge and nasal obstruction, reported by 95% and 90%, respectively; the most prevailing observation during nasal endoscopy was middle meatus purulent discharge, noticed in 58% of the patients. Maxillary sinus was most often affected, seen in 65% of the patients on a CT scan, and 40% had obstruction of the osteomeatal complex on CT imaging. The nasal endoscopy had a sensitivity of 73.3%, specificity of 85.3%, positive predictive value of 92.7%, and negative predictive value of 55.8%. The research also found no significant differences in positive predictive value (PPV) between nasal endoscopy and CT scan. In contrast, the sensitivity of nasal endoscopy was significantly greater than that of CT scan. Conclusion: The study found that nasal endoscopic findings for patients with positive clinical features were purulent (cream-colored) discharge and middle meatus polyps, which is sufficient for diagnosing chronic rhinosinusitis; the study showed that Nasal endoscopy is almost as accurate as CT scans and CT scan findings are well correlates with sinus endoscopy, due to its precision, cheap cost, and radiation dosage.